The Illusion of Renewal in Sherchan’s “New Year” - Bhandari, Nagendra Bahadur (The Outlook: Journal of English Studies, 2026)
This article examines how Bhupi Sherchan’s poem "New Year" destabilizes the conventional association of the New Year with renewal, exposing the instability of meanings attached to temporal change. The existing scholarship on Sherchan’s poetry discusses the use of day-to-day language, social irony, and socio-political engagement, drawing on thematic and contextual analysis. Departing from such readings, this article focuses on the internal dynamics of language and meaning. Through the theoretical lens of Jacques Derrida’s deconstruction, particularly the concept of différance, this article explores how the poem deconstructs the culturally dominant notion of temporal renewal. It examines the patterns of repetition, binary oppositions, figurative disruptions, and rhetorical tensions within the poem in a qualitative interpretive methodological approach. The analysis reveals that the poem not only shows disillusionment with the cyclic process of time; it also demonstrates how the very idea of “newness” is perpetually deferred, undermining reference to the stable meaning. Difference, absence, and contradiction used in the poem generate meaning that remains inherently deferred, unstable, and open to continual reinterpretations. This study reveals the intrinsic instability of meaning while reexamining Sherchen’s poetic practice. It contributes to expanding the critical practices in Nepali literary scholarship with a focus on language, textuality, and philosophical inquiry.